Academic Journals: Policies, Trends and Issues - Moyer, R. Charles; Crockett, John H. (Academy of Management Journal, 1976)
The article presents the results of a survey of journal editors on acceptance rates, publication lags and editorial practices of scholarly journals. Information was obtained in a June 1975 mail survey of journal editors in the areas of management, business and economic research. The authors of the survey have provided an evidence regarding acceptance rates and publication lags in key management and business journals. They have found that acceptance rates have declined during the 1970 to 1974 period. They also found that review and publication lags have grown. It was also found that the fee journals provide more manuscript critique that nonfee journals.